Colonic Phenotype of the Ileum in Crohn's Disease: A Prospective Study Before and After Ileocolonic Resection. Issue 9 (22nd July 2014) - Ascolani, Marta; Mescoli, Claudia; Palmieri, Giampiero; Sica, Giuseppe; Calabrese, Emma; Petruzziello, Carmelina; Onali, Sara; Albertoni, Laura; Lolli, Elisabetta; Condino, Giovanna; Pallone, Francesco; Rugge, Massimo; et al.
Abstract : Background: Colonic metaplasia has been described in pouchitis. In a prospective study, we investigated whether colonic phenotype may develop in Crohn's disease (CD) ileum. The expression of sulfomucins (colonic mucin), sialomucins, and CD10 (small intestine mucin and phenotype) was evaluated before and after ileocolonic resection for CD. Methods: From February 2007 to March 2010, 22 patients with CD undergoing surgery were enrolled. Clinical (Crohn's Disease Activity Index >150) and endoscopic recurrence (Rutgeerts score ≥1) rates were assessed at 6 and 12 months. Ileal samples were taken at surgery (T0), at 6 (T1), and 12 months (T2) for histology, histochemistry (High Iron Diamine-Alcian Blue), and immunohistochemistry (anti-CD10). Results: In 22 patients, recurrence was assessed at 6 and 12 months (clinical recurrence 9% and 18%; endoscopic recurrence 73% and 77%). In all 22 patients, ileal samples were taken at 6 and 12 months (involved area in patients with recurrence). In 19 of 22 (86.3%) patients, the involved ileum was also studied at surgery. At T0, T1, and T2, the expression of sialomucins and CD10 (small intestine mucin and phenotype) was comparable and higher ( P < 0.0001) than the expression of sulfomucins (colonic mucin) (mean [range], T0:82 [35–100] versus 75 [0–100] versus 16 [0–50]; T1:96 [60–100] versus 94.7 [50–100] versus 3.89 [0–40]; T2:93.3 [60–100] versus 88.1 [25–100] versus 6.6 [0–40]). The expression of small-intestine mucin and phenotype was higher at T1 ( P = 0.025) versus T0 ( P = 0.026). Differently, the expression of colonic mucin was lower at T1 versus T0 ( P = 0.027). Conclusions: In CD, the ileum involved by severe/established lesions develops a "metaplastic" colonic mucosa phenotype. Differently, CD ileum with no lesions or with early recurrence maintains the "native" small intestine type mucin secretion and phenotype.